(untitled) (Revista Contexto & Saúde, 2026)
Objective: To map evidence regarding follow-up care within the healthcare system for children born to women diagnosed with syphilis during pregnancy. Methods: A scoping review was conducted in accordance with JBI and PRISMA-ScR. Primary studies from four electronic databases were included, with language restrictions to Portuguese, English, and Spanish, and no time restrictions. Results: A total of 283 documents were retrieved. Following selection stages, 19 were analyzed—most originating from Brazil and all published between 2011 and 2024. Evidence regarding follow-up care is presented based on the following themes: Diagnostic tests for syphilis and associated damage; Pharmacological treatment; Follow-up within the Healthcare Network; and Social support. Conclusion: Follow-up care was found to be compromised, notably due to inconsistencies regarding diagnosis and pharmacological treatment, as well as poor coordination within the care network. This network operated under a disease-centered approach that failed to adequately account for the determinants of life and health.